Association between serum 25-hydroxyvitamin D and osteoarthritis: A national population-based analysis of NHANES 2001–2018 - Yu, Guoyu; Lin, Yuan; Dai, Hanhao; Xu, Jie; Liu, Jun (Frontiers in Nutrition, 2023)
Background Previous studies have not provided a consensus on the effect of serum 25-hydroxyvitamin D [25(OH)D] on osteoarthritis (OA). We aimed to evaluate the association using a large, nationally representative sample. Methods The cross-sectional data were obtained from the 2001 to 2018 National Health and Nutrition Examination Survey (NHANES). Individuals aged ≥40 years who had information of serum 25(OH)D, self-report OA, and related covariates were included. Multivariable logistic regression analysis was employed to assess the association between serum 25(OH)D and osteoarthritis. Results Among the 21,334 participants included (weighted mean age, 56.9 years; 48.5% men), the proportion of participants with high serum 25(OH)D concentrations (≥100 nmol/L) increased significantly from 4.2% in 2001–2006 to 18.8% in 2013–2018. Higher serum 25(OH)D levels were associated with more osteoarthritis prevalence in fully adjusted model (odd ratio [OR] 1.25 [95% CI: 1.10, 1.43] for the 50–75 nmol/L group; OR 1.62 [95% CI: 1.42, 1.85] for the 75–100 nmol/L group; OR 1.91 [95% CI: 1.59, 2.30] for the ≥100 nmol/L group; with <50 nmol/L group as the reference) (p < 0.001 for trend). The association was consistent across several sensitivity analyses, including propensity score methods and excluding participants who had received vitamin D supplement. In subgroup analysis, the OR for the association increased significantly with body mass index (BMI) (BMI < 25 kg/m2, 1.01 [95% CI: 1.04, 1.08]; BMI 25–30 kg/m2, 1.05 [95% CI: 1.01, 1.08]; BMI ≥ 30 kg/m2, 1.10 [95% CI: 1.06, 1.13]; p = 0.004 for interaction). Conclusion There was a positive correlation between serum 25(OH)D and osteoarthritis with a possible modification by BMI. Our finding raises concerns about the potential adverse effects of high serum 25(OH)D on osteoarthritis, particularly among obese individuals. More well-designed studies are still needed to validate our findings in future.